2003
DOI: 10.1023/a:1025480418721
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: Two sequenced nodulation regions of lupin Bradyrhizobium sp. WM9 carried the majority of genes involved in the Nod factor production. The nod region I harbored: nolA, nodD, nodA, nodB, nodC, nodS, nodI, nodJ, nolO, nodZ, fixR, nifA, fixA, nodM, nolK and noeL. This gene arrangement resembled that found in the nodulation region of Bradyrhizobium japonicum USDA110, however strain WM9 harbored only one nodD gene copy, while the nodM, nolK and noeL genes had no counterparts in the 410 kb symbiotic region of strain … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
20
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(22 citation statements)
references
References 43 publications
1
20
0
Order By: Relevance
“…The ad hoc Committee for the Re-evaluation of the Species Definition in Bacteriology (Stackebrandt et al, 2002;Gevers et al, 2005) suggested the sequence analysis of a set of protein-encoding genes as alternative phylogenetic markers, or multilocus sequence analysis (MLSA). Several recent studies have confirmed that sequences from housekeeping genes can be used for identification at the species level (Wertz et al, 2003;Zeigler, 2003), for evolutionary population genetics and in taxonomy (Stepkowski et al, 2003;Vinuesa et al, 2005a,b;Bailly et al, 2006). The analysis of a small number of carefully selected gene sequences may equal or even surpass the precision of DNA-DNA hybridization for the quantification of genome relatedness and this approach thus has the potential to replace cumbersome DNA-DNA hybridizations (Zeigler, 2003, Martens et al, 2008.…”
Section: Introductionmentioning
confidence: 98%
“…The ad hoc Committee for the Re-evaluation of the Species Definition in Bacteriology (Stackebrandt et al, 2002;Gevers et al, 2005) suggested the sequence analysis of a set of protein-encoding genes as alternative phylogenetic markers, or multilocus sequence analysis (MLSA). Several recent studies have confirmed that sequences from housekeeping genes can be used for identification at the species level (Wertz et al, 2003;Zeigler, 2003), for evolutionary population genetics and in taxonomy (Stepkowski et al, 2003;Vinuesa et al, 2005a,b;Bailly et al, 2006). The analysis of a small number of carefully selected gene sequences may equal or even surpass the precision of DNA-DNA hybridization for the quantification of genome relatedness and this approach thus has the potential to replace cumbersome DNA-DNA hybridizations (Zeigler, 2003, Martens et al, 2008.…”
Section: Introductionmentioning
confidence: 98%
“…The Mediterranean basin is the centre of origin of this monospecific genus (Allen & Allen, 1981). B. pelecinus forms a highly specific nitrogen-fixing symbiotic association with bacteria that have been classified within the genus Mesorhizobium (Howieson et al, 1995; Nandasena et al, 2001 Nandasena et al, , 2004 The locus dnaK encodes a highly conserved chaperone protein with multiple cellular functions, and this gene has proven to be a useful diagnostic tool for root-nodule bacteria (Stepkowski et al, 2003;Eardly et al, 2005). A 300 bp intragenic fragment from the variable region of dnaK was amplified and sequenced using the primers TSdnaK2 and TSdnaK3 (Stepkowski et al, 2003 and WSM1540) differed by only 1 or 2 bp.…”
mentioning
confidence: 99%
“…B. pelecinus forms a highly specific nitrogen-fixing symbiotic association with bacteria that have been classified within the genus Mesorhizobium (Howieson et al, 1995; Nandasena et al, 2001 Nandasena et al, , 2004 The locus dnaK encodes a highly conserved chaperone protein with multiple cellular functions, and this gene has proven to be a useful diagnostic tool for root-nodule bacteria (Stepkowski et al, 2003;Eardly et al, 2005). A 300 bp intragenic fragment from the variable region of dnaK was amplified and sequenced using the primers TSdnaK2 and TSdnaK3 (Stepkowski et al, 2003 and WSM1540) differed by only 1 or 2 bp. These Biserrula mesorhizobia had >99.3 % sequence similarity to M. ciceri and <91.9 % sequence similarity to M. loti and, as a consequence, all 14 Biserrula mesorhizobia given in Table 1 clustered with M. ciceri when a phylogenetic tree was developed (not shown) using the available partial dnaK sequences of type strains of root-nodule bacteria.…”
mentioning
confidence: 99%
See 2 more Smart Citations